Prevalence of functioning difficulties and disability in Mexican adolescent women and their populational characteristics - Betania Allen-Leigh (Salud Pública de México, 2017)
Objective . Report prevalence of functioning difficulties and disabilities among Mexican adolescent women 15-17 years old and identify differences in characteristics of those with and without a functioning difficulty or disability Materials and methods . Using data from the National Survey of Boys, Girls and Women in Mexico 2015 we estimated prevalence of functioning difficulties and disability and used chi square tests for independence and logistic regression to explore associations between this condition and various character - istics. Results . Of Mexican adolescent women 15-17 years old, 11.1% had a functioning difficulty or disability. The group of domains of functioning difficulty and disability with by far the highest prevalence was socio-emotional and behavioral functioning difficulties or disability with 8.6%. Being employed, rural residence and self-reported depression symptoms were associated with having functioning difficulties or disability. Conclusions . This survey constitutes an important initial step in collecting data on functioning difficulty and disability in Mexico although larger samples should be studied.